PENGARUH BRAND AMBASSADOR AKTOR KIM SEON HO TERHADAP MINAT BELI KONSUMEN PRODUK SKINCARE EVERWHITE DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING - Farrel, Muhammad; Sunaryo, Sunaryo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The more sophisticated the technology for disseminating information, the faster the flow of information will reach the public. People nowadays are fond of Korean culture thanks to information procurement access and speed. Companies are following the trend and using Korean celebrities as their brand ambassadors; Everwhite, an Indonesian skincare company, is one of them. The objective of this explanatory research is to identify the effect of brand ambassador on the purchase intention of Everwhite consumers with the mediation of brand image. Using non-probability sampling method and purposive sampling technique, 100 people who know about Kim Seon Ho and Everwhite were selected as the sample. The results of the data analysis in SPSS 26 have led to findings that brand ambassador has a positive and significant effect on brand image and purchase intention, that brand image positively and significantly influences purchase intention, and that brand image does not mediate the effect of brand ambassador on purchase intention. The results of this study are effective in increasing buying interest from potential Everwhite consumers.